2020
DOI: 10.33963/kp.15551
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan in the treatment of patients with acute cardiac conditions: an expert opinion of the Association of Intensive Cardiac Care of the Polish Cardiac Society

Abstract: Levosimendan is a new inodilator which involves 3 main mechanisms: increases the calcium sensitivity of cardiomyocytes, acts as a vasodilator due to the opening of potassium channels, and has a cardioprotective effect. Levosimendan is mainly used in the treatment of acute decompensated heart failure (class IIb recommendation according to the European Society of Cardiology guidelines). However, numerous clinical trials indicate the validity of repeated infusions of levosimendan in patients with stable heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…In addition, there was a trend towards lower 6-month mortality on levosimendan. Taking into account the promising results of our meta-analysis and the cardioprotective effects of levosimendan demonstrated in multiple studies, there is a need for a well-designed multicenter randomized placebo-controlled study, including an adequately large group of outpatients with acute HF to ultimately determine the effect of levosimendan on long-term prognosis [8].…”
Section: This Paper Was Guest Edited By Prof Togay Evrinmentioning
confidence: 99%
“…In addition, there was a trend towards lower 6-month mortality on levosimendan. Taking into account the promising results of our meta-analysis and the cardioprotective effects of levosimendan demonstrated in multiple studies, there is a need for a well-designed multicenter randomized placebo-controlled study, including an adequately large group of outpatients with acute HF to ultimately determine the effect of levosimendan on long-term prognosis [8].…”
Section: This Paper Was Guest Edited By Prof Togay Evrinmentioning
confidence: 99%
“…We describe a life-threatening acute-on-chronic PE treated with CDT supported by levosimendan infusion. We showed that levosimendan may have favorable effects on RV contractility in acute settings [4][5].…”
Section: Repeated Episodes Of Pe Can Persistently Increase Pap and De...mentioning
confidence: 77%
“…Levosimendan, compared to other inotropes, reduces the signs and symptoms of HF [3,[5][6][7][8], and mortality [5,7,8]. However, metanalyses [9,10] and the SURVIVE study [11] showed that levosimendan does not reduce mortality.…”
Section: Resultsmentioning
confidence: 99%